ASEAN and the multilateral trading system. - STEPHENSON, Sherry M. (1994)
Focuses on how ASEAN promotes Southeast Asia's expanding role in GATT. Notes that individual members of ASEAN have been remarkably successful traders, but not as a result of ASEAN. ASEAN's two greatest achievements have been to provide a framework for regional stability, and to create a unified voice for the conduct of external relations with the rest of the world.